Prevalence and associated factors of sexual violence experienced by housemaids in Ethiopia: a systematic review and meta-analysis - Birye Dessalegn Mekonnen; Zemene Habtu Lakew; Endalkachew Belayneh Melese (BMC, 2022)
Plain language summary Sexual violence is the most common form of gender-based violence and has been a persistent problem in public health. Housemaids are the most vulnerable groups for any of the forms of sexual violence, as they face the greatest obstacles to gaining protection and necessary services. The sexual activity of domestic workers differs from that of the general population. Housemaids are more likely to be coerced into having sex and to have had sex before age 15 as compared to other young women. Housemaids often experience sexual violence by a person unknown to the victim, employers and male members of the household, brokers, or other intermediary persons. Sexual violence against housemaids remains usually concealed as victims cannot report such offenses. The most common reason for not reporting such violence was a lack of awareness of where to and for whom to report, a low level of education, and a fear of losing their work as they have few or no options for other work. In Ethiopia, the national prevalence of sexual violence among housemaids is not investigated. Also, forms and determinants of sexual violence and identification of perpetrators have not been well described. Thus, a systematic review and meta-analysis was conducted to estimate the pooled prevalence of sexual violence amongst housemaids in Ethiopia. This systematic review and meta-analysis revealed that nearly half of housemaids experienced at least one form of sexual violence by different perpetrators. Of the forms of sexual violence against housemaids, sexual harassment is high. Male employers are the vast majority of perpetrators of their housemaids. Thus, concerned stakeholders should develop and implement interventions that could empower housemaids in their struggle toward the elimination of sexual violence, create awareness for men, and prompt punishment of the perpetrators.